Socializing Agents of Sexuality: Group of Friends - Balarezo-López, Gunther (2023)
At all ages, people are affected by the social group with which they frequently associate and with which they wish to identify. This influence is greater during childhood and the first part of adolescence, which is the time of greatest psychological plasticity. Peer influences on behavior become more important as children get older and have more sustained and close relationships with other children their age.